Ict in primary school: theories and practices in the mother tongue - Quadros-Flores, Paula (2019)
Change processes taking place nowadays, particularly the interests and motivations of the new generation who now attends school, require the renewal of pedagogical practices of teachers and therefore the attention of their trainers in University. The teaching practice (pedagogic stage) is a privileged time for curricular integration of ICT integration of theory and practice during the orientation process made by the first author. We developed during an academic year an exploratory study. The data were collected in the reports of teachers' training, in the orientation sessions and in the observation of the pedagogical practice of these teachers in primary school. The analysis was made through the content analysis. We have selected for this article some student teacher practices that are integrative activities focused on the learning of the mother tongue. Thus, we present: a) theoretical guidelines for the use of ICT in the mother tongue in Primary School; b) examples of curriculum integration of ICT in this context; c) integration of this work in pedagogical practices of student teachers; d) the reflexive and critical ideas expressed by these teachers. Finally, we discuss the need to develop in an integrated way digital literacy, reading and writing. Thus, we intend to contribute to a widening of educational discourse in the panorama of the initial teacher training